2005
DOI: 10.1248/cpb.53.836
|View full text |Cite
|
Sign up to set email alerts
|

A New Phytoecdysteroid from Ajuga taiwanensis

Abstract: Many plants contain ecdysteroids, polyhydroxysteroids with a cis-fused A/B ring junction and 14a-hydroxy-7-ene-6-one system, structurally related with ecdysone, the biosynthetic precursor of the insect moulting hormone.1) These compounds exhibit interesting physiological activities such as regulation of moulting in insects, hormonal functions involve regeneration, metamorphosis, reproduction and differentiation in all arthropods, and antiulcer, antirheumatic, insulin regulation and diuretic or tonic effects in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…HPLC-MS-ESI showed a molecular ion peak of [M + Na] + m/z 519.3 corresponding to C 27 H 44 O 8 . HPLC-MS-ESI and NMR data are in agreement with literature reported for the isolated ecdysteroids (Okuzumi et al 2005;Chan et al 2005;Darwish and Reinecke 2003).…”
Section: Isolation Of Phytoecdysteroids From In Vivo a Turkestanicasupporting
confidence: 90%
See 1 more Smart Citation
“…HPLC-MS-ESI showed a molecular ion peak of [M + Na] + m/z 519.3 corresponding to C 27 H 44 O 8 . HPLC-MS-ESI and NMR data are in agreement with literature reported for the isolated ecdysteroids (Okuzumi et al 2005;Chan et al 2005;Darwish and Reinecke 2003).…”
Section: Isolation Of Phytoecdysteroids From In Vivo a Turkestanicasupporting
confidence: 90%
“…The isolated phytoecdysteroids were identified by comparing physical, chemical and spectral data ( 1 H and 13 C NMR and ESI-MS) with reported data (Okuzumi et al 2005;Chan et al 2005;Darwish and Reinecke 2003). 1 H NMR (500 MHz) and 13 C NMR (125 MHz) spectra, all in CD 3 OD, were recorded on a Varian Inova 500 spectrometer (Varian Instruments, Palo Alto, CA), using TMS as the internal standard.…”
Section: Extraction and Isolation Of Phytoecdysteroidsmentioning
confidence: 99%
“…Crystal data for 1: C 28 H 28 N 4 O 5 , M = 500.54, orthorhombic, space group P212121 (no. 19), a = 8.18580 (10) The final R 1 was 0.0675 (I > 2σ(I)) and wR 2 was 0.1981 (all data). The goodness of fit on F 2 was 1.074.…”
Section: X-ray Crystal Structure Analysismentioning
confidence: 93%
“…Its13 C NMR and DEPT data (Table1) showed the presence of 35 carbon resonances, including four methyls, eight methylenes, and fourteen methines (six olefinic carbons), as well as nine quaternary carbon atoms (two olefinic carbons, three carbonyls, and four aliphatic carbons). Detailed analysis of its 1D and 2D NMR allowed for the assignment of three partial structures, including a typical ecdysteroid substructure with a cis-fused A/B ring junction and a 14α-hydroxy-7-ene-6-one skeleton[9], a γ-lactone side chain[10], and a monosubstituted benzoate group. All the above data taken together indicated that 2 was structurally related to the γ-lactone phytoecdysteroids 29-norcyasterone[11], with the only difference being the hydroxy substitution at C-22.…”
mentioning
confidence: 99%
“…A literature survey indicates that 29 new ecdysteroids have been reported from the Lamiaceae family. These are 28- epi -cyasterone [(22 R ,24 S ,25 S ,28 S ) 5 β -stigmast-7-ene-26-oic acid, 2 β ,3 β ,14,20,22,28-hexahydroxy-6-oxo- γ -lactone] ( 152 ), isolated from Eriophyton wallchii 115 , ajugalide-E ( 153 ) from Ajuga taiwanensis 116 , breviflorasterone ( 154 ), ajugacetalsterone C ( 155 ), ajugacetalsterone D ( 156 ) from Ajuga macrosperma var. breviflora 117 , decumbesterone A ( 157 ) 118 and ajugacetalsterone E ( 158 ) 119 isolated from Ajuga decumbens , 22-dehydrocyasterone-2-glucoside ( 159 ), ajugacetalsterone A ( 160 ) and ajugacetalsterone B ( 161 ), isolated from Ajuga nipponensis 120 , 25-hydroxy-atrotosterone A ( 162 ), 11-hydroxy-cyasterone ( 163 ), 11-hydroxy-sidisterone ( 164 ), turkesterone 22-acetate ( 165 ), 22 oxo-turkesterone ( 166 ), 11-hydroxy-Δ24-capitasterone ( 167 ) and turkesterone 20,22-acetonide ( 168 ), isolated from Ajuga turkestanica 121 , reptanslactone A ( 169 ), reptanslactone B ( 170 ) and sendreisterone ( 171 ), isolated from Ajuga reptans var.…”
Section: New Naturally Occurring Phytoecdysteroids Reported Since 1999mentioning
confidence: 99%